More Than 20 Centimeters of Intracardiac Cement Removed After Kyphoplasty - Talal Alomar; Deepti Boddupalli; Kevin Brady; Randeep Sandhu; Ranjani Behara; Sammy Alomar (Annals of Internal Medicine: Clinical Cases)
Intracardiac cement embolization through the venous system is a potentially deadly complication of the vertebroplasty and kyphoplasty. We present a case involving a 55-year-old woman who exhibited dyspnea on exertion, chest pain, and back pain 2 weeks after a kyphoplasty of the T12 vertebrae. The patient had open-heart surgery to remove a winding intracardiac segment of cement more than 20 cm long. Our review of the literature suggests this is one of the largest intracardiac cement emboli removed to date.